PBL-Based Health Communication Case Teaching in Higher Education: A Case Study of Peking University’s "Youth Talk" Tobacco Control Campaign - Chen, Yu; Zheng, Huimin; Xu, Jing (The Journal of Medicine, Humanity and Media, 2025)
This case study examines the design and practice of Problem-Based Learning (PBL) in health communication teaching at universities, using Peking University’s "Youth Talk" tobacco control campaign as an exemplar. The study systematically investigates the implementation process and effectiveness evaluation through SWOT analysis, questionnaire surveys, and media monitoring. Findings reveal that PBL case teaching significantly enhances students’ tobacco control cognition and attitudes, effectively cultivates practical health communication capabilities, promotes youth participation in building a healthy China, and expands the social influence of tobacco control advocacy. This case provides an innovative model and replicable experience for health communication practical teaching in higher education, offering practical value for advancing the "Healthy China 2030" strategic objectives.